2002
DOI: 10.1002/jbm.a.10275
|View full text |Cite
|
Sign up to set email alerts
|

Titanium surface topography alters cell shape and modulates bone morphogenetic protein 2 expression in the J774A.1 macrophage cell line

Abstract: Macrophage cytokine expression significantly affects wound healing. Macrophage secretion of transforming growth factor beta 1 (TGFbeta1) and bone morphogenetic proteins (BMP) may affect osteogenesis at endosseous implant surfaces. The aim of this investigation was to determine the effect of commercially pure titanium (cpTi) substrate topography on adherent macrophage osteogenic and osteoinductive cytokine expression. J774A.1 murine macrophage cell adhesion was examined by scanning electron microscopy, 0-72 h f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 61 publications
8
107
0
1
Order By: Relevance
“…6, p < 0.05), suggesting that these cells can also impact osteogenesis directly in response to osteoinductive surface structure, as others have previously suggested (Fellah et al, 2007). In vitro, inflammatory macrophages secrete osteogenic factors such as oncostatin M (OSM) (Guihard et al, 2012;Nicolaidou et al, 2012) and may also express BMPs (Champagne et al, 2002;Takebe et al, 2003;Honda et al, 2006). In vivo, Omar et al (2011) showed that a titanium screw coated with lipopolysaccharide (LPS) to stimulate classical activation of macrophages resulted in higher bone contact when in orthotopic sites (Omar et al, 2011) though it is unknown what impact classically activated macrophages may have on bone formation in ectopic sites.…”
Section: Nl Davison Et Al Surface Architecture Of Tricalcium Phosphatementioning
confidence: 84%
“…6, p < 0.05), suggesting that these cells can also impact osteogenesis directly in response to osteoinductive surface structure, as others have previously suggested (Fellah et al, 2007). In vitro, inflammatory macrophages secrete osteogenic factors such as oncostatin M (OSM) (Guihard et al, 2012;Nicolaidou et al, 2012) and may also express BMPs (Champagne et al, 2002;Takebe et al, 2003;Honda et al, 2006). In vivo, Omar et al (2011) showed that a titanium screw coated with lipopolysaccharide (LPS) to stimulate classical activation of macrophages resulted in higher bone contact when in orthotopic sites (Omar et al, 2011) though it is unknown what impact classically activated macrophages may have on bone formation in ectopic sites.…”
Section: Nl Davison Et Al Surface Architecture Of Tricalcium Phosphatementioning
confidence: 84%
“…However, large doses of BMPs are required to stimulate substantial amounts of de novo bone formation, likely rendering basal levels of BMPs circulating in the blood ineffective in achieving this response (van Baardewijk et al, 2013;Yuan et al, 2010). Alternatively, BMPs or other osteogenic factors may originate from (pre-)osteoclast interactions with microstructured surfaces including CaP (Davison et al, 2014b) and titanium (Takebe et al, 2003). Elevated Ca 2+ levels resulting from osteoclast resorption of a mineralised substrate can also stimulate BMP expression of precursor cells (Barradas et al, 2012;Klar et al, 2013).…”
Section: Nl Davison Et Almentioning
confidence: 99%
“…Mag. X400 the material (Anderson et al, 2004;Lu et al, 2002;Solheim et al, 2002;Takebe et al 2003;Xia & Triffitt, 2006). Particles that are smaller than the macrophages themselves (< 10 µm) can be easily phagocytosed.…”
Section: Deposition Of Titanium and Zirconium In Organs With Macrophamentioning
confidence: 99%